2021
DOI: 10.3390/agriculture11080713
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Potentially Toxic Metals in Egyptian Alluvial Soils, Berseem Clover (Trifolium alexandrinum L.), and Groundwater after Long-Term Wastewater Irrigation

Abstract: The reduced availability of water resources in Egypt has imposed the need to intensify the use of wastewater for crop irrigation in the alluvial soils of anthropogenic origin. Relevant effects can derive from contents of potentially toxic metals (PTMs) in supply resources soils, crops, and groundwater in these areas. For this reason the PTM content has to be monitored to evaluate and minimize health hazards. Therefore, in this context, two areas of the SE Nile Delta subjected to 25 year of wastewater irrigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 61 publications
2
15
1
Order By: Relevance
“…This interpretation could be confirmed by lower metal partitioning in the available fraction reported for other soil types under sewage irrigation. In the Nile Delta TypicTorriorthent soils, mean DTPA-extractable contents were 1.98 mg kg −1 for Pb [39] and 1.01 mg kg −1 for Zn [40].…”
Section: Metal Concentrations In the Irrigated Soilsmentioning
confidence: 96%
See 1 more Smart Citation
“…This interpretation could be confirmed by lower metal partitioning in the available fraction reported for other soil types under sewage irrigation. In the Nile Delta TypicTorriorthent soils, mean DTPA-extractable contents were 1.98 mg kg −1 for Pb [39] and 1.01 mg kg −1 for Zn [40].…”
Section: Metal Concentrations In the Irrigated Soilsmentioning
confidence: 96%
“…For instance, in TypicHaplosalid and VerticTorrifluvent soils in the Northern Nile Delta, Aitta et al [46] reported that AR for Mn did not exceed 1%. Moreover, Abuzaid et al [40] reported that ARs for Pb and Zn in TypicTorriorthent soils of the South-Eastern Nile Delta did not exceed 10 and 2%, respectively.…”
Section: Metal Geo-accumulation and Availability Ratiomentioning
confidence: 99%
“…In this study, while selecting this practice for the agricultural cycle, it was necessary to pay attention to the following matters: (1) It is preferable not to reuse a particular site to grow the same type of plants that were planted on it in the previous season or in recent seasons, especially when growing seasonal plants, such as vegetables and medicinal herbs, or when replanting perennial trees, such as fruit trees and shrubs [56,[59][60][61]. (2) The ideal practice is to plant different types and varieties of seasonal crops in different locations and basins, and not to replant the same crop in the same location or basin until after a few years, as this practice helps in controlling harmful and vascular insects.…”
Section: Discussionmentioning
confidence: 99%
“…(2) The ideal practice is to plant different types and varieties of seasonal crops in different locations and basins, and not to replant the same crop in the same location or basin until after a few years, as this practice helps in controlling harmful and vascular insects. Crop rotation also eliminates weeds and maintains soil fertility and good levels of organic matter [55][56][57][58][59][60][61]. Crops that are similar in their predisposition to the same diseases, and in their susceptibility to harmful insects, should be planted at spaced intervals [62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation